Cancer-Associated Fibroblast-Derived Exosomal miRNA-320a Promotes Macrophage M2 Polarization In Vitro by Regulating PTEN/PI3Kγ Signaling in Pancreatic Cancer. (1st July 2022) - Zhao, Mingkun; Zhuang, Aobo; Fang, Yuan
Abstract : Our previous study has indicated that cancer-associated fibroblasts (CAFs) play a crucial role in regulating gemcitabine resistance through transferring exosomal miRNA-106b to cancer cells. Tumor-associated macrophages (TAMs) are recently verified to facilitate gemcitabine resistance. However, the effect of CAFs in regulating TAMs function in pancreatic cancer (PCa) remains unclear. Here, primary CAFs were extracted from tumor tissues of PCa patients, and CAFs-derived exosomes (CAFs-Exo) were acquired and authenticated by transmission electron microscopy, qNano, and western blot analysis. The role of exosomal miRNA-320a in facilitating macrophage M2 polarization was investigated in vitro . We found that CAFs-derived conditioned medium (CM) possessed a higher potential to promote macrophage M2 polarization compared with normal fibroblasts (NFs) or PCa cell-derived CM. Furthermore, CAFs-Exo treatment polarized macrophage to M2 phenotype. miRNA-320a levels were remarkably increased in CAFs-Exo versus NFs-Exo. More important, miRNA-320a could be transferred from CAFs to macrophages through exosomes, and miRNA-320a overexpression in macrophages facilitated its M2 polarization. Functionally, miRNA-320a-overexpressed macrophages facilitated PCa cell proliferation and invasion. CAFs pretreated with miRNA-320a inhibitor reduced miRNA-320a expression in CAFs-Exo and led to decreased M2 macrophage polarization. Finally, we verified that miRNA-320a polarized macrophage to M2 phenotype by regulating PTEN/PI3K γ signaling. Taken together, the current data demonstrated that CAFs-derived exosomal miRNA-320a facilitated macrophage M2 polarization to accelerate malignant behavior of PCa cells.